Between care and coercion: asylum seekers’ experiences with COVID-19 containment and mitigation measures in German reception centres - Rast, Eilin; Perplies, Clara; Biddle, Louise; Bozorgmehr, Kayvan (International journal of public health, 2023)
Objectives: COVID-19 containment and mitigation measures have been criticised for amplifying pre-existing individual and structural vulnerabilities among asylum seekers. We qualitatively explored their experiences with and attitudes towards pandemic measures to inform people-centred responses in future health emergencies. Methods: We interviewed eleven asylum seekers in a German reception centre (July-December 2020). The semi-structured interviews were recorded, transcribed, and analysed thematically with an inductive-deductive approach. Results: Quarantine was experienced as burdensome by participants. Shortcomings in social support, everyday necessities, information, hygiene, and daily activities exacerbated the strains of quarantine. Interviewees held different opinions about the usefulness and appropriateness of the various containment and mitigation measures. These opinions differed by individual risk perception and the measures’ comprehensibility and compatibility with personal needs. Power asymmetries related to the asylum system furthermore impacted on preventive behaviour. Conclusions: Quarantine can amplify mental health burdens and power asymmetries and can therefore constitute a considerable stressor for asylum seekers. Provision of diversity-sensitive information, daily necessities, and accessible psychosocial support is required to counteract adverse psychosocial impacts of pandemic measures and safeguard well-being in this population.
Gesehen am 24.05.2023